Analysis of the Recycling Sector in Intermediate Cities . Study Case – Neiva, Colombia (2020)
(Eng) The economic activity of recycling belongs to an unfortunate and marginalized segment of society in Colombia. This fact translates in high rates of informality and a general perception about people that work in this activity, which come usually from extreme poverty, bu rdened by discrimination, drug addiction, and rejection. The goal of this research was to determine the most significant factors impacting levels of society and economics. For this purpose, we carried out a mixed analysis in the chain of the recycling sect or in Neiva, an intermediate city. Because of the informality of waste pickers’ union, official information and field survey were conducted to identify the waste commercialization establishments. The collection and transportation process were identified, a nd a survey was applied to 50 waste pickers and ten recycling companies. Seventy - two percent of the population is constituted by male gender, older than 25 years, in an unsafe condition, and with labor intensity of 8 hours per day (average). On the other h and, forty percent of companies have labor - related personnel, which confirms a high level of informality in the sector. The most commercialized product is cardboard, and the vast majority only purchase and commercialize the material